1987
DOI: 10.1346/ccmn.1987.0350402
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Bidimensional Zeolitic Structures Obtained from Synthetic Beidellite and Hydroxy-Aluminum Solutions

Abstract: Abstract--Beidellite was synthesized hydrothermally from a noncrystalline gel at 320~ and 130 bar pressure. The beidellitic character of the product was verified by infrared spectroscopy on the NH4 § exchanged form. Intercalation was achieved with hydroxy-aluminum solutions having different OH/A1 molar ratios. The solutions were investigated by several methods, including 27A1 nuclear magnetic resonance. Essentially, two Al species were detected: monomeric A1 and a polymerized form containing A1 in four-fold co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
4

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(65 citation statements)
references
References 27 publications
3
58
0
4
Order By: Relevance
“…This hypothesis is, however, based on pillaring with solutions that contain a range of A1 polymers, and has been challenged by more recent findings. Indeed, (1) pillaring can also be achieved with solutions that do not contain the Keggin ion (Schoonheydt et al 1993); and (2) the typical spacing of 1.8-1.9 nm becomes visible only after washing (Schutz et al 1987;Schoonheydt and Leeman 1992;Figueras et al 1990), indicating important reorganisation of the adsorbed A1 species upon washing of the pillared clays.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is, however, based on pillaring with solutions that contain a range of A1 polymers, and has been challenged by more recent findings. Indeed, (1) pillaring can also be achieved with solutions that do not contain the Keggin ion (Schoonheydt et al 1993); and (2) the typical spacing of 1.8-1.9 nm becomes visible only after washing (Schutz et al 1987;Schoonheydt and Leeman 1992;Figueras et al 1990), indicating important reorganisation of the adsorbed A1 species upon washing of the pillared clays.…”
Section: Introductionmentioning
confidence: 99%
“…Farmer et al (1991aFarmer et al ( , 1991b found that saponite-and nontronite-like structures developed from aluminosilicate precipitates digested at 20~176 in solutions containing Mg and Fe ions, respectively. On the other hand, beidellite has been synthesized from aluminosilicate gel in NaOH solutions at 300~176 (Plee et al, 1987;Schutz et al, 1987). Kloprogge et al (1990) carried out hydrothermal synthesis of beidellite from aluminosilicate gel in NaOH solutions with a pH range from 7.5 to 13.5 at a temperature of 350~ They reported that the most highly crystallized beidellite was obtained at 350~ 1 kbar, 5 days of reaction, and a pH of 10 in the starting solution.…”
Section: Introductionmentioning
confidence: 99%
“…However, the disadvantage of organic pillars is the low thermostability and the resulting collapse of the pillared clay structure. The use of inorganic compounds, such as A1 (Brindley & Sempels, 1977;Lahav et al, 1978;Plee et al, 1987;Schutz et al, 1987), and Zr (Vaughan et al, 1979; * Present address: TNO-TPD-TU Delft, Dept. of Inorganic Materials Chemistry, PO Box 595, 5600 AN Eindhoyen, The Netherlands.…”
mentioning
confidence: 99%